2016
DOI: 10.1158/1541-7786.mcr-16-0175
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Genetic, Epigenetic, and Transcriptional Profiling Identifies Molecular Pathways in the Development of Laterally Spreading Tumors

Abstract: The novel genetic, epigenetic, and transcriptional changes associated with LST development reveal important insights into why some adenomas do not progress to cancer. The finding that LSTs exhibit a mutational load similar to colorectal carcinomas has implications for the validity of molecular biomarkers for assessing cancer risk. Mol Cancer Res; 14(12); 1217-28. ©2016 AACR.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 39 publications
3
20
1
Order By: Relevance
“…To date, functional roles for AnkB have been implicated in neuronal disease, diabetes, and cancer. 6163 AnkB, along with many other cardiac ion channel-related proteins, is also expressed in neurons. AnkB −/− mice are born with severe neurological defects including brain and optical nerve malformation.…”
Section: Future Investigationsmentioning
confidence: 99%
“…To date, functional roles for AnkB have been implicated in neuronal disease, diabetes, and cancer. 6163 AnkB, along with many other cardiac ion channel-related proteins, is also expressed in neurons. AnkB −/− mice are born with severe neurological defects including brain and optical nerve malformation.…”
Section: Future Investigationsmentioning
confidence: 99%
“…This suggests that RGMb acts as a tumor suppressor, possibly by inhibiting SMAD activation. This idea is also supported by the observation that the RGMb gene is inactivated by frame-shift mutations in a subtype of colorectal cancer [67].…”
Section: Box 2 Mutations and Knockouts Of Rgmsmentioning
confidence: 73%
“…22 Recent studies suggested epigenetic changes of SLITRK5 may be an early event in colorectal neoplasia. 6 Specifically, we found 4 genes (IRF4, FLI1, KDR and NRG1) within the CGC with hypermethylated DMRs. As illustrated in Supporting Information Figure S2b, methylation levels of FLI1 and KDR, two vascular epithelial growth factor (VEGF) family members, were significantly increased in LST comparing to matched normal samples.…”
Section: Lsts Exhibited Hallmark Dna Methylation Abnormality Around Tsssmentioning
confidence: 74%
“…Some of the differentially methylated sites (CNTN1 and SLITRK5) were reported in previous studies, demonstrating the reliability and robustness of our analysis pipeline. 6 CNTN1 regulates cell surface interactions in the nervous system and participates in the Notch pathway. 19 Previous studies suggest that CNTN1 promotes tumor invasion and metastasis in multiple cancers.…”
Section: Lsts Exhibited Hallmark Dna Methylation Abnormality Around Tsssmentioning
confidence: 99%